Origin laundering by professional fraud facilitators, challenges and opportunities for Customs - Murphy, David (2014)
Highlights the activities of professional Customs fraud facilitators, their central role in origin laundering, and in particular their impact in terms of revenue loss and the circumvention of trade policy measures.